Developing a naval design and engineering platform (2005)
Due to the increase in complexity in production operations, and the low delivery times required by the current market in the naval sector, it is necessary to handle CAD / CAE applications that acquire the role of integrators between the design, planning and manufacturing processes In a newly built vessel the amount of information that is handled is very high, being managed entirely in two dimensions until reaching the last phase of the project, prior to manufacturing, where the development of steel in three dimensions is already beginning to be common. Therefore, during the evolution of the project, a 3D representation of the complete ship is not available at any time, forcing numerous modifications to be made once the ship is already built, thus raising the cost of its manufacture and delaying delivery times. Such modifications could be avoided with a 3D model that allows simultaneous visualization of all its components, just as it is when it is already built.